Effects of High and Low Doses of Folic Acid on the Soluble Receptor Activator of Nuclear Factor-kappa B Ligand/Osteoprotegerin Ratio during Pregnancy - Nazila FATHI MAROUFI; Amir GHORBANIHAGHJO; Manizheh SAYYAH MELLI; Maryam VAEZI; Zohreh HEKMATI AZAR MEHRABANI; Maryam BANNAZADEH AMIRKHIZ; Nadereh RASHTCHIZADEH (Tehran University of Medical Sciences, 2017)
Background: Pregnancy Associated Osteoporosis (PAO) can lead to serious difficulties such as fragility fractures, elongated back pain and height loss in affected women. Soluble Receptor Activator of Nuclear Factor-Kappa B ligand (sRANKL) to Osteoprotegerin (OPG) ratio is chosen as a bone metabolism equation in many bone diseases characterized by bone resorption, such as post-menopausal osteoporosis and would be modiﬁed with folic acid supplementation. This study was done to compare the effects of high dose (5mg/day) and low dose (0.5 mg/day) folic acid in the RANKL/OPG ratio and Tumor Necrosis Factorα (TNFα) concentration during pregnancy. Methods: Forty-five pregnant women who visited the AL-Zahra Hospital, Tabriz Iran, from September 2013 to November 2014 were assigned into two groups in this randomized, double-blind, clinical trial, included women who took 5 mg/day (group1) and who took 0.5 mg/day (Group 2) folic acid supplementation before pregnancy until 36th pregnancy. The biochemical variables in serum of pregnant women were measured before and at the end of the study. The study was registered in the Iranian Registry of Clinical Trials (IRCT) as ID, IRCT2013122315903N1. Results: OPG levels were signiﬁcantly higher compared with the baseline value (P=0.008), although sRANKL (P<0.001), TNFα (P=0.005) and sRANKL/OPG ratio (P<0.001) reduced significantly with high dose of folic acid supplementation. A signiﬁcant positive correlation was observed between the decreased RANKL and TNFα levels (r=0.451, P=0.031) at the end of study in high dose group. Conclusion: High dose of folic acid supplementation could decrease bone resorptive biomarkers and may prevent PAO in pregnant women by increasing OPG and decreasing sRANKL and TNFα.